1981
DOI: 10.1128/aac.19.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Cefmenoxime (SCE-1365), a novel broad-spectrum cephalosporin: in vitro and in vivo antibacterial activities

Abstract: The activity of cefmenoxime (SCE-1365), 7,8-[2-(2-aminothiazol-4-yl)-(Z)-2-methoxyiminoacetamido]-3-[(1-methyl-1H-tetrazol-5-yl)thiomethyl]ceph-3-em-4-carboxylic acid, was compared with that of other cephalosporins. Cefinenoxime exhibited high activity against a wide variety of gram-positive and gramnegative bacteria. The in vitro activity of cefmenoxime against Streptococcus pyogenes, Haemophilus influenzae, and Enterobacteriaceae, including indolepositive Proteus, Serratia marcescens, Enterobacter cloacae, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…Like cefotaxime, cefmenoxime displays a broad spectrum of activity against both gram-positive and gram-negative bacteria in vitro (3, 8, 10, ime has greater activity than cefotaxime in mice infected with various species of the family Enterobacteriaceae (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like cefotaxime, cefmenoxime displays a broad spectrum of activity against both gram-positive and gram-negative bacteria in vitro (3, 8, 10, ime has greater activity than cefotaxime in mice infected with various species of the family Enterobacteriaceae (12).…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent studies, however, have shown that the outcome of E. coli infections in this model treated with cefotaxime is not significantly better than that of a conventional therapeutic regimen, ampicillin-gentamicin (K. S. Kim, submitted for publication). Recently, Tsuchiya et al (12) have shown that cefmenoxime, a new cephalosporin structurally similar to cefotaxime, has greater protective and therapeutic activities than cefotaxime against members of the family Enterobacteriaceae in mice despite their similar activities in vitro. The present study was therefore performed to examine the activity of cefmenoxime in vitro and in vivo against E. coli and to compare the results with those of cefotaxime and ampicillin.…”
mentioning
confidence: 99%
“…Ceftriaxone demonstrates good activity against Haemophilus sp., Neiserria gonorrheae, and Neisseria meningitidis and is generally as active as cefotaxime and moxalactam against members of the Enterobacteriaceae (4,19). Broad in vitro activity has also been observed with cefmenoxime (25,27). Cefsulodin was first introduced as an antipseudomonal cephalosporin (26) and, compared with other cephalosporins, is less active than ceftazidime but more active than cefoperazone or cefmenoxime against P. aeruginosa (10,26,27).…”
mentioning
confidence: 99%
“…Several investigators have reported that B. fragilis strains produce a ,B-lactamase which has cephalosporinase activity and that it plays a significant role in the resistance of these organisms to B-lactam compounds (2,11,13,17,22). On the other hand, several newlactam compounds have been developed in recent years for the treatment of infections caused by resistant organisms which produce a ,-lactamase (1,7,9,20). Prominent among such compounds are cefoxitin, cefmetazole, moxalactam, and cefotetan, which are grouped as 7a-methoxy cephalosporins, and cefotaxime, ceftizoxime, and cefmenoxime, which are included in the 7p-methoxyiminoacetamido cephalosporin group.…”
mentioning
confidence: 99%